2018
DOI: 10.3390/machines6020018
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle Avoidance System for Unmanned Ground Vehicles by Using Ultrasonic Sensors

Abstract: Artificial intelligence is the ability of a computer to perform the functions and reasoning typical of the human mind. In its purely informatic aspect, it includes the theory and techniques for the development of algorithms that allow machines to show an intelligent ability and/or perform an intelligent activity, at least in specific areas. In particular, there are automatic learning algorithms based on the same mechanisms that are thought to be the basis of all the cognitive processes developed by the human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…Tie-cable regulation is usually independent of the actuators used for the LDA deployment [38][39][40] and from the control system [41][42][43][44]. Here, the method to regulate tie cable tension in an antenna with rigid ring truss support is first described.…”
Section: Rigid Ring Truss Support: Construction Length Determinationmentioning
confidence: 99%
“…Tie-cable regulation is usually independent of the actuators used for the LDA deployment [38][39][40] and from the control system [41][42][43][44]. Here, the method to regulate tie cable tension in an antenna with rigid ring truss support is first described.…”
Section: Rigid Ring Truss Support: Construction Length Determinationmentioning
confidence: 99%
“…Another key challenge in path planning is obstacle avoidance. Systems designed for this purpose can be used to assist human vehicle operators or on fully autonomous vehicles (De Simone et al, 2018;Liu et al, 2018). One type of obstacle-avoidance system uses local data about the vehicle's environment to control steering to avoid obstacles.…”
Section: Automatic Vehicle Guidance and Steering Controlmentioning
confidence: 99%
“…Sensors [6] are of different types like color, gas, ultrasonic, touch, PIR, IR, humidity, heartbeat. Among these, the authors use an ultrasonic sensor [3] shown in Fig.1 because it is cost-effective and reliable. Usually, this sensor is used to recognize the barrier.…”
Section: B Sensormentioning
confidence: 99%